Estudo do reprocessamento de terpolímeros ABS - Pagliarussi, Marcelo Sanches (1997)
This study studied the effects of reprocessing on the terpolymer acrylonitrile-butadiene-styrene (ABS). ABS presents an intrinsic instability to oxidative, thermal or photochemically initiated degradation. Therefore, we sought to adopt a methodology for thermal restabilization of ABS, through the use of different commercial thermal stabilizers (always in the form of a blend of phenolic antioxidants and phosphites in a ratio of 1:2, respectively), and to study the effects of restabilization on the overall performance of the material. The study was divided into two stages: pre-selection of formulations and accelerated thermal aging. In the pre-selection, processing tests were performed to evaluate the processing stability of the four formulations used in relation to the reprocessed regrind without restabilization. Multiple-pass tests were performed with monitoring of the flow index and processing simulation tests on the Haake torque rheometer. The four samples with restabilization (formulations 1-4) and the non-restabilized regrind showed essentially the same stability characteristics, with no significant differences between the samples. In any case, formulation 2 was chosen to proceed, together with the regrind, to the accelerated aging test, due to its flow stability according to the evaluations of fluidity index and torque stability in the Haake Torque Rheometer. Test specimens for tensile and impact tests were injected from formulation 2 and the regrind, and these were subjected to the accelerated thermal aging test, in an oven with air circulation, at 100°C, for 1000 hours. After this period, the unaged (to) and aged (ti) specimens were characterized by monitoring their mechanical properties, and the samples from the granulated reprocessed material (pellets) to the aged c.p. (ti) were characterized by differential scanning calorimetry (DSC) and infrared spectroscopy with attenuated total reflectance (FTIR-ATR). It was observed that the ABS terpolymer presents good reprocessing conditions, despite its low thermooxidative stability. The material presented a small variation in the fluidity index, demonstrating that the thermooxidative degradation did not cause significant changes in molecular weight. On the other hand, degradation manifested itself quickly in the polybutadiene (PB) phase, indicating that, in the long term, it can cause a significant decrease in impact resistance. The behaviors were very similar, both in the restabilized sample (formulation 2) and in the ground sample without restabilization.